Challenges of the management team in the fight Against covid-19: Experience report (Research, Society and Development, 2021)
Objective: To report the challenges faced by the management team of a secondary-level hospital service in the interior of the State of São Paulo, in the face of the COVID-19 pandemic. Material and methods: a descriptive, quantitative and experience report type study, which portrays the challenges faced by the management team regarding the training of the institution's professionals and the dimensioning of the nursing team in the period from February to March 2020. Results: The management team needed to use strategies in the training of health care professionals and the administrative department in the use and adherence of PPE, since there was a lack of knowledge about the transmission of the virus and the scarcity of individual protection supplies on the market. As for the dimensioning of nursing professionals, the selection of employees to compose the scale-followed criteria considered pre-defined in conjunction with the institution's management, such as: the qualification in the care of critical patients and the time of exposure to the virus in the workplace. Conclusion: The scarcity of PPE in the months of February and March, and of qualified professionals and the high workload of the nursing team were challenges that health services faced since the beginning of the pandemic, so it was necessary to have strategies for the patient and for the nursing team, in order to guarantee the well-being, quality and safety of all those involved in the assistance.